Students’ Perception on Watching Fantasy Films to Improve Speaking Skills - Rahmadin Agus, Muhammad Darell (ELITE JOURNAL, 2023)
ABSTRACT The purpose of this Research to investigate if English speaking skills of the students can be improved by watching fantasy films.The research method used is descriptive quantitative, for this research participation is all faculties of the As-Syafi'iyah Islamic University. For the data collection technique here, we use a questionnaire And Interview that has been made on Google Form in the form of a statement with a response reaching 30 And Interview interview it can be for 5 students As-syafi’iyah Islamic of University with 10 Questions. For the data analysis technique, we use percentages. then for the percentage results as follows. Questionnaire 1 Agree : 35.3% disagree : 64.7%. Quetionnaire 2 Agree : 45.7% Disagree : 54.3%. Quetionnaire 3 Agree : 85.7 % Disagree : 14.3 %. Quetionnaire 4 Agree : 51.4% Disagree : 48.6%. Questionnaire 5 Agree : 76.5 % Disagree : 23.5%. Quetionnaire 6 Agree : 94.3 % Disagree : 0%. Quetionnaire 7 Agree : 91.4 % Disagree : 8.6%. Quetionnaire 8 Agree : 57.6% Disagree : 42.4%. Quetionnaire 9 Agree : 54.3 % Disagree : 45.7%. Questionnaire 10 Agree : 94.3 % Disagree : 0%. From this result, it is confirmed that some of these students agree that watching this fantasy film can improve their speaking English skills and also from some of the students there are also those who do not like watching fantasy films, even many of them do not often watch this fantasy film. Keywords: Fantasy Movies, Speaking Skills, Descriptive Quantitative.